2019
DOI: 10.1093/asj/sjz003
|View full text |Cite|
|
Sign up to set email alerts
|

Liquid Formulation of AbobotulinumtoxinA: A 6-Month, Phase 3, Double-Blind, Randomized, Placebo-Controlled Study of a Single Treatment, Ready-to-Use Toxin for Moderate-to-Severe Glabellar Lines

Abstract: BackgroundSafety and efficacy of botulinum toxin A for glabellar line (GL) treatment are well established. Currently approved formulations require reconstitution before injection.ObjectivesThe authors sought to assess 6-month efficacy, safety, and patient satisfaction of new ready-to-use abobotulinumtoxinA solution for injection (ASI) in patients with moderate-to-severe GL at maximum frown.MethodsThe authors conducted a phase 3, double-blind, randomized, placebo-controlled trial (NCT02353871). Patients (N = 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 27 publications
5
29
0
1
Order By: Relevance
“…The recent phase 3 trial in GL reported high rates of treatment response with ASI compared with placebo, by both investigator and patient assessment (88.3% and 76.0% at day 29, respectively; P < 0.0001 compared with placebo for both), as well as a long duration of response and a safety profile comparable with that of reconstituted abobotulinumtoxinA (Ipsen Ltd; Azzalure). 17 During the previous phase 2 comparator and placebo-controlled study, similar efficacy results were observed for both ASI and reconstituted abobotulinumtoxinA. 16 This was the first phase 3 clinical trial to include scales from the FACE-Q, a validated PRO instrument, to assess patient satisfaction with BoNT-A treatment for GL.…”
mentioning
confidence: 69%
See 4 more Smart Citations
“…The recent phase 3 trial in GL reported high rates of treatment response with ASI compared with placebo, by both investigator and patient assessment (88.3% and 76.0% at day 29, respectively; P < 0.0001 compared with placebo for both), as well as a long duration of response and a safety profile comparable with that of reconstituted abobotulinumtoxinA (Ipsen Ltd; Azzalure). 17 During the previous phase 2 comparator and placebo-controlled study, similar efficacy results were observed for both ASI and reconstituted abobotulinumtoxinA. 16 This was the first phase 3 clinical trial to include scales from the FACE-Q, a validated PRO instrument, to assess patient satisfaction with BoNT-A treatment for GL.…”
mentioning
confidence: 69%
“…The study protocol and achievement of primary and secondary endpoints were previously published. 17 In brief, this was a phase 3, randomized, double-blind, placebo-controlled trial with a follow-up period of 6 months that was conducted at 9 study centers across France and Germany between January 2015 and August 2015 (NCT02353871). Eligible patients were aged between 18 and 65 years (men and nonpregnant women), were botulinum toxin-naïve, and presented with moderate or severe (grade 2 or 3) vertical GL at maximum frown by investigator’s live assessment (ILA; 4-point photographic scale) and patient’s self-assessment (SSA; 4-point categorical scale) at baseline.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations